ترقية دوافع تعلم اللغة العربية بالتعليم القائم على المهام - Rosiyadi, Meylda; Arifin, Syamsul; Alawiyah, N. Lalah (Kalimatuna: Journal of Arabic Research, 2023)
This study departs from the problem of decreasing motivation to learn Arabic and the lack of effective learning techniques used by teachers in learning. This study aims to obtain an overview of increasing motivation to learn Arabic with assignment-based learning. This study uses the Classroom Action Research method with the theory of Kemmis & MC Tagrt with a sample of 20 people. In each cycle, this research is focused on obtaining data on increasing motivation to learn Arabic for the fifth grade students of MIS Nurul Huda Caringin Bogor for the 2022/2023 academic year by using assignment-based learning. The data collection technique used is the distribution of questionnaires and questionnaires. Analysis of this research data with combined analysis, namely the quantitative technique based on the average score of the motivation questionnaire and the questionnaire score, while the qualitative technique is based on the description of the results of the analysis of the average score of the motivation questionnaire and the questionnaire score. The results of this study will prove that this assignment technique can increase the motivation to learn Arabic for the fifth grade students of MIS Nurul Huda Caringin-Bogor.